2009
DOI: 10.1177/0022034509356512
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of PTGS2 Promoter Methylation in Chronic Periodontitis

Abstract: Levels of prostaglandin E 2 and the prostaglandin-endoperoxide synthase-2 (PTGS2, or COX-2) increase in actively progressing periodontal lesions, but decrease in chronic disease. We hypothesized that chronic inflammation is associated with altered DNA methylation levels within the PTGS2 promoter, with effects on COX-2 mRNA expression. PTGS2 promoter methylation levels from periodontally inflamed gingival biopsies showed a 5.06-fold increase as compared with non-inflamed samples (p = 0.03), and the odds of meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
108
2
5

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(122 citation statements)
references
References 21 publications
7
108
2
5
Order By: Relevance
“…The levels of prostaglandin E and the prostaglandin-endoperoxide synthase-2 (PTGS2) increase in progressing periodontal lesions, but decrease in chronic disease. It was reported that expression of the PTGS2 gene decreases in chronic periodontitis due to promoter hypermethylation (Zhang et al, 2010).…”
Section: Epigenetics In Human Diseases and Agingmentioning
confidence: 99%
“…The levels of prostaglandin E and the prostaglandin-endoperoxide synthase-2 (PTGS2) increase in progressing periodontal lesions, but decrease in chronic disease. It was reported that expression of the PTGS2 gene decreases in chronic periodontitis due to promoter hypermethylation (Zhang et al, 2010).…”
Section: Epigenetics In Human Diseases and Agingmentioning
confidence: 99%
“…Several authors have investigated the role of epigenetics in chronic or aggressive periodontitis [36][37][38], and have demonstrated that the expression levels of cytokines and chemokines [39], toll-like receptors [40], protease-activated receptors [41], interleukin-8 [42], and cyclooxygenase-2 [37,38] could be affected by oral bacteria. A recent study documented that the presence of different oral bacteria resulted in a differential methylation profile in gingival epithelia [43], while another article demonstrated hypomethylated oral epithelia in patients with generalized aggressive periodontitis [36].…”
Section: Dna Methylationmentioning
confidence: 99%
“…[73] Cytokines such as IL6 and interferon gamma (IFNγ) were found to be overexpressed in inflamed tissues of chronic periodontitis patients. [70,74] Zhang et al reported that hypomethylation of the IFNγ promoter may lead to increased IFNγ transcription in chronic periodontitis, thus resulting in IFNγ overexpression. [70] In contrast, genes such as tumor necrosis factor alpha (TNFa) and cyclooxygenase-2 were hypermethylated at the CpG site which represses expression.…”
Section: Manifestation Of Epigenetic Mechanisms In Oral Diseases Perimentioning
confidence: 99%
“…[70] In addition, it was found that chronic inflammation is related to altered DNA methylation levels.…”
Section: Manifestation Of Epigenetic Mechanisms In Oral Diseases Perimentioning
confidence: 99%